CHILDREN WITH DISABILITIES IN EDUCATION AND THEIR PARENTS’ PARTICIPATION PREPARATION - Yagovkina, Larisa; Dubovskaya, Vera; Kiseleva, Maria; Egorova, Natalya; Dmitrievsky, Lyudmila (Revista Inclusiones, 2020)
The article provides an overview of philosophical and humanitarian approaches to training parents in an inclusive education and the training system itself. The study purpose is to substantiate, develop and test a system for preparing parents of children with disabilities for assistance in the education, based on the humanistic approach and the axiological concept of philosophy.